An Analysis Of The Role Of Learning Discipline As A Mediator Between Learning Motivation And Academic Achievement In Economics Among Students Of Sma Negeri 8 Padang - Astuti, Widya; Serli Diovani Teza (The Future of Education Journal, 2025)
This study aims to analyze the role of learning discipline as a mediating variable in the relationship between learning motivation and students’ academic achievement in Economics at SMA Negeri 8 Padang. Field observations indicate a gap between students’ high learning motivation and their suboptimal academic performance, suggesting the presence of an intervening factor within the learning process. A quantitative approach was employed using a survey method and path analysis technique. Data were collected through questionnaires distributed to 120 11th-grade social science students and analyzed using statistical software to test the relationships among variables. The findings reveal that learning motivation has a positive and significant effect on learning discipline, and both variables simultaneously have a significant impact on students’ academic achievement. Learning discipline was found to be a significant mediating variable that strengthens the influence of motivation on academic performance. In other words, students with high motivation who lack disciplined study habits tend not to achieve optimal learning outcomes. The study concludes that learning discipline plays a crucial role in bridging students’ internal motivation and their academic success. These findings emphasize the importance of fostering structured and consistent learning behaviors to improve student achievement, especially in subjects that require conceptual understanding and logical reasoning such as Economics. This research is expected to contribute to the development of more effective, character-oriented learning strategies.